The p53 R72P polymorphism does not affect the physiological response to ionizing radiation in a mouse model. Issue 12 (18th June 2017) - Domínguez, Emily R.; Orona, Jennifer; Lin, Kevin; Pérez, Carlos J.; Benavides, Fernando; Kusewitt, Donna F.; Johnson, David G.
ABSTRACT: Tissue culture and mouse model studies show that the presence of the arginine (R) or proline (P) coding single nucleotide polymorphism (SNP) of the tumor suppressor gene p53 at codon 72 ( p53 R72P) differentially affects the responses to genotoxic insult. Compared to the P variant, the R variant shows increased apoptosis in most cell cultures and mouse model tissues in response to genotoxins, and epidemiological studies suggest that the R variant may enhance cancer survival and reduce the risks of adverse reactions to genotoxic cancer treatment. As ionizing radiation (IR) treatment is often used in cancer therapy, we sought to test the physiological effects of IR in mouse models of the p53 R72P polymorphism. By performing blood counts, immunohistochemical (IHC) staining and survival studies in mouse populations rigorously controlled for strain background, sex and age, we discovered that p53 R72P polymorphism did not differentially affect the physiological response to IR. Our findings suggest that genotyping for this polymorphism to personalize IR therapy may have little clinical utility.